Parental Antecedents of Locus of Control of Reinforcement: A Qualitative Review - Carton, John S.; Ries, Mikayla; Nowicki, Stephen (Frontiers in Psychology, 2021)
The construct of locus of control of reinforcement has generated thousands of studies since its introduction as a psychological concept by Julian Rotter (1966). Although evidence indicates its importance for a wide range of outcomes, comparatively little research has been directed toward identification of potential developmental antecedents of internal/external expectancies. A previous review of antecedent findings (Carton & Nowicki, 1994) called for more research to be completed, particularly using observational and/or longitudinal methodologies. The current paper summarizes and critiques antecedent research published in the intervening years since Carton and Nowicki’s review. We conclude with recommendations for future research and advice for those trying to promote the development of appropriate internal control expectancies in children.